PENDAMPINGAN PEMBUATAN MEDIA PEMBELAJARAN DENGAN APLIKASI VIDEO SCRIBE UNTUK GURU MA NU HASYIM ASY’ARI 2 - Muhammad Noor Ahsin; Mila Roysa (Universitas Muria Kudus, 2020)
At the MA NU Hasyim Asy'ari 2 School, the teacher is still having trouble making an interesting computer-based interactive learning media. Referring to the problem, there is a need for training and assistance in making interesting, interactive computer-based learning media for Indonesian language teachers. One alternative to improve the ability of teachers to make learning media is to train and provide assistance for teachers to create learning media. One interesting application that can be used to make interactive and interesting learning videos is the Scribe video application. The results of community service assistance provided to teachers at MA Hasyim Asy'ari shows that teachers are capable and skilled at making learning media with video scribe applications. The Scribe video application is expected to be able to provide teacher skills to create attractive computer-based learning media. MA NU Hasyim Asy'ari 2 Teacher, Gebog Kudus District, has become more creative in creating interesting learning media.